Geschäftsmodelle als Ausgangspunkt für das Preismanagement im KV. - Stölzle, Wolfgang; Resch, Bettina (Deutscher Verkehrs-Verl., 2009)
Der Kombinierte Verkehr (KV) Straße/Schiene steht im harten Wettbewerb mit reinen Straßengütertransporten. So führen aus Sicht der Verlader gezielte Preisvergleiche häufig zur bevorzugten Auswahl des Straßengüterverkehrs. In der Folge wird der KV nicht selten als preislich unattraktive Alternative wahrgenommen, wobei die Preisunterschiede anbieterseitig i. d. R. mit einem höheren Kostenniveau aufgrund des Verkehrsträgerwechsels sowie kostenintensiven Vor- und Nachläufen begründet werden. Vor diesem Hintergrund widmet sich der Beitrag besonderen Herausforderungen des Preismanagements im KV.

Growing horizontal and vertical competition in intermodal transport (IT) involving road and rail, coupled with forwarders' rising marketing standards, necessitate closer cooperation among all the IT participants. Although customers tend to view the IT product as being fully comprehensive, it is nonetheless created in a work-sharing arrangement by several participants who traditionally coordinate market prices on a bilateral basis after earlier individual negotiations. This purely market-oriented course of action does highlight the danger of prices being calculated without due consideration for the needs of a given market. The IT sector may thus be at a competitive disadvantage. Obviously, the aspect of price - as a determining factor when IT services are being marketed - is continuously enhancing its role yet has hardly been given due consideration by individual IT participants so far. Apart from purposeful reductions in operational costs, price levels aimed at specific target groups are likely to boost customers' awareness of attractive IT services on offer. An IT price management system should, therefore, reach beyond a given company. It is against this background that our report evaluates well-specified requirements for an IT price management system. On account of the multitude of heterogeneous IT services on offer, a thorough description of IT-related business models can serve as a starting point for our analysis. A specially selected type of business model helps to show ~the challenges that need to be met effectively when a price management system in intermodal transport is being devised.
Business models to serve as starting points for price management in intermodal transport.
Keywords: Verkehr; Schienengüterverkehr; Straßengüterverkehr; Kostenberechnung; Gebrochener Verkehr; Wettbewerb; Preispolitik; Vermarktung; Kostenmanagement; Wettbewerbsfähigkeit; Transportleistung; Geschäftsmodell